Recurrent Occipital Seizures with Transient MRI Changes - Mohankumar Kurukumbi; Allison Jacobs (Case Reports in Neurological Medicine)
Peri-ictal magnetic resonance imaging (MRI) findings following seizure activity are a recognized phenomenon that is not well understood (Cole, 2004). Transient changes are not usually expected to be present in postictal MRI studies because of their rarity. Here, we present a unique case of peri-ictal MRI findings located in the occipital lobe, present in a 34-year-old female with recurrent occipital seizures occurring twice in four years. MRI changes completely resolved after both episodes with no residual focal damage. The peri-ictal occipital changes on MRI in this patient are unique because they have been captured on more than one occasion. Peri-ictal MRI findings are a known phenomenon with unknown pathophysiology, although attempts have been made to understand these findings. Though the MRI findings and presentation appear to be stroke-like or PRES-like, seizures should be kept in the differential for better treatment outcomes.